The impact of regional remittances on economic growth in Mexico: a dynamic space-time panel approach - Mendoza-Cota, Jorge Eduardo; Torres-Preciado, Víctor Hugo (Papeles de Población; Vol. 25 Núm. 101 (2019): Papeles de Población, 2019)
The international economic literature indicates that remittances represent a determinant for macroeconomic stability as well as a source of financial resources, in particular for developing economics. The empirical evidence regarding the impact of remittances on economic growth is inconclusive. The objective of this paper is to show the short and long term effects of remittances on economic growth. A spatial dynamic space-time panel model was implemented to estimate the direct effects of remittances and the presence of interregional diffusion effects. The results suggest that remittances have had a positive effect on economic growth of the receiving states, with important effects on neighboring states. In addition, private credit had positive effects when interregional economic networks are present.